Major Issues in Simulating Some Arctic Snowpack Properties Using Current Detailed Snow Physics Models: Consequences for the Thermal Regime and Water Budget of Permafrost. (5th January 2019) - Domine, Florent; Picard, Ghislain; Morin, Samuel; Barrere, Mathieu; Madore, Jean‐Benoît; Langlois, Alexandre
Abstract: Accurately simulating the physical properties of Arctic snowpacks is essential for modeling the surface energy budget and the permafrost thermal regime. We show that the detailed snow physics models Crocus and SNOWPACK cannot simulate critical snow physical variables. Both models simulate basal layers with high density and high thermal conductivity, and top layers with low values for both variables, while field measurements yield opposite results. We explore the impact of an inverted snow stratigraphy on the permafrost thermal regime at a high Arctic site using a simplified heat transfer model and idealized snowpacks with three layers. One snowpack has a typical Arctic stratification with a low‐density insulating basal layer, while the other (called Alpine‐type snowpack ) has a dense conducting basal layer. Snowpack stratification impacts simulated ground temperatures at 5 cm depth by less than 0.3 °C. Heat conduction through layered snowpacks is therefore determined by thermal insulance rather than by stratification. Ground dehydration caused by upward water vapor diffusion is 4 times greater under Arctic stratification, leading to a larger latent heat loss, but also to a lower soil thermal conductivity caused by ice loss, so that the overall effect of dehydration on ground temperature is uncertain. Snowpack stratification is found to affect snow surface temperature by up to 4 °C. Lastly, different snow metamorphism rates lead to a lower Alpine snowpack albedo, contributing to a warmer ground. Quantifying all these effects is needed for adequately simulating permafrost temperature. This requires the development of a snow and soil model that describes water vapor fluxes. Plain Language Summary: Many detailed snow physics models were developed mostly for alpine conditions. They do not reproduce the strong upward water vapor flux between the lowest snow layers in contact with the warmer ground and the upper snow layers in contact with the colder atmosphere, which occurs in the Arctic. As a consequence, snow density and thermal conductivity are not adequately simulated for Arctic conditions. Models predict high density, high thermal conductivity basal snow layers, while the opposite is observed in the Arctic. We show that, if the total insulating capacity of the snowpack is simulated correctly, having an incorrect layering of thermal conductivity in the simulated snowpack has little impact on ground temperature. However, since current models do not simulate the upward water vapor flux, the water vapor loss of the ground in winter cannot be simulated either. This affects the soil water budget and therefore its physical properties, and this may modify its temperature. Incorrect snow layering is also found to affect snow surface temperature by up to 4 °C. Key Points: The detailed snow physics models Crocus and SNOWPACK do not simulate adequately physical properties of Arctic snowpacks such as thermal conductivity Incorrect thermal conductivities of snow layers do not affect ground temperature if the snowpack thermal insulance is correctly simulated Incorrect thermal conductivities of snow layers however modifies the simulated soil water budget, the soil thermal conductivity, and the snow surface temperature